Two new species of Entoloma (Entolomataceae) from Khyber Pakhtunkhwa, Pakistan - Izhar, Aiman; Usman, Muhammad; Kiran, Munazza; Khalid, Abdul Nasir (Phytotaxa, 2022)
Cedar towering forests of Kumrat Valley, Khyber Pakhtunkhwa, Pakistan were visited on several occasions to collect mushrooms and this resulted in the discovery of two novel species of Entoloma. Entoloma kumraticus is characterized by bluish-brown, centrally depressed pileus, serrulate lamellar edge, bluish-violet fibrillose stipe, dense clusters of cheilocystidia, and presence of abundant grayish-brown intracellular pigments in the terminal cells of pileipellis, and cheilocystidia. Entoloma dirensis is characterized by brownish olive to dull violet, finely fibrillose striate pileus with a violet-blue margin, slightly twisted violet-blue stipe, and blackish-brown lamellar edge, with groups of cheilocystidia which are often septate. The new species are presented based on the morphological and molecular study. Entoloma kumraticus and E. dirensis formed distinct phylogenetic lineages based on the sequences of nuclear ribosomal ITS and LSU gene regions. A key to the Pakistani species in sect. Cyanula is also provided.